Ecosystem Impacts and Productive Capacity of a Multi-Species Pastured Livestock System - Rowntree, Jason E.; Stanley, Paige L.; Maciel, Isabella C. F.; Thorbecke, Mariko; Rosenzweig, Steven T.; Hancock, Dennis W.; Guzman, Aidee; Raven, Matt R. (Frontiers in Sustainable Food Systems, 2020)
Regenerative agriculture (RA) is a newly codified approach to agriculture that emphasizes reducing reliance on exogeneous inputs as well as restoring and enhancing ecosystem services such as soil carbon (C) sequestration. These RA principles suggest that modern livestock systems can be redesigned to better capitalize on animals’ ecological niche as biological up cyclers, and may be necessary to fully regenerate some landscapes. One example is a multi-species pasture rotation (MSPR) system, which symbiotically stacks multiple animal production enterprises (i.e. chickens, cattle, sheep, and pigs) on one landscape. We conducted a whole-farm life cycle assessment (LCA) of a MSPR in the southeastern U.S. that was originally converted from degraded cropland. We compared the production outputs, greenhouse gas emissions (GHGs), land footprints, and soil health outcomes to a conventional, commodity (COM) production system of each respective species. Our 20-year MSPR chronosequence of soil C and other soil health indicators shows dramatic improvement since establishment, sequestering an average of 2.29 Mg C ha-1 yr-1. Incorporation of soil C sequestration into the LCA reduced net GHG emissions of the MSPR by 80%, resulting in a footprint 66% lower than COM. However, when comparing required land between the two systems for food production, MSPR required 2.5 times more land when compared to COM. Thus, while our model indicates that MSPR can simultaneously produce protein while regenerating land, a considerably greater land area is needed when compared to COM. Our results present an important yet paradoxical conclusion on land and food production balance. Should society prioritize an input-intensive, COM system that produces more food from a smaller yet degrading land base? Or, alternatively, should systems like MSPR that produce less food on a larger, but more ecologically functional landscape be more highly prioritized? These complexities must be considered in the global debate of agricultural practice and land. Our results indicate MSPRs are a useful model for alternative livestock production systems with improved environmental outcomes, but in this study may present considerable land-use tradeoffs.